Evaluation of SARS-CoV-2 Humoral Response Following Vaccination with ChAdOx1 nCoV-19 (Covishield™) and/or Sinopharm, BBIBP-CorV (Vero cell™) - Kamar, Sher Bahadur; Pandey, Hemraj; Shahi, Ramesh; Puri, Shurehraman; Yadav, Gopal Kumar; Amgain, Kapil (Journal of Nepal Health Research Council, 2024)
Background: Billions of doses of COVID-19 vaccine have been introducing in the world to prevent pandemic COVID-19. Higher efficacy but limited data are available for its longevity. We aimed to find out the IgG Anti-SARS Cov-2 antibody level among frontline healthcare workers after two doses of vaccines.Methods: A cross-sectional study was carried among 170 HCPs of Seti Provincial Hospital of western Nepal, who were more than 18 years, and had taken two doses of either one of COVID 19 vaccine. All those participants, who were on leave during the data collection tenure (1st February 2022 to 28th February 2022) and/or did not consent to participate were excluded. Mindray SARS-CoV-2 S-RBD IgG assay kit based on CLIA method, was used whose target antigen is S-RBD (spike protein of receptor binding domain) antigen. The IgG immunoglobulin is detected and cut off value ?10 AU/ml is considered positive.Results: Based on the recommended cut off, the antibody was present in more than 90% across both groups of vaccinee i.e. the positive antibody titer at a mean duration of 7.31 months was 93.53% overall (93.75% and 93.44% in Vero cell™ and Covishield™ vaccinees respectively).There were 3.92 times high odds of high antibody titer (?250 AU/ml) in Covishield™ group (OR: 3.92, 95% CI: 1.86-8.26, P-value: <0.001) than in Vero cell™ group of vaccinee. Similarly, there were significant difference of high titer of antibody across groups with more than six months of elapse of vaccination (OR: 2.18, 95% CI: 1.06-4.49, P-value: <0.001) than with less than six months of elapse of vaccination.Conclusions: The humoral response was higher among HCPs who received two-doses vaccination with ChAdOx1 nCoV-19 (Covishield™) and/or Sinopharm, BBIBP-CorV (Vero cell™) vaccine, and among those with six or more months of elapse of vaccination. The seroprevalence of SARS-CoV-2 following two-doses vaccination among HCPs was more than nine-tenths. Keywords: antibody immunity; ChAdOx1 nCoV-19(Covishield™); receptor binding domain; seroprevalence; sinopharm.